Psychometric development and validation of personal growth initiative scale across male and female in early adulthood population in Pakistan: a comparative study - Zahid, Bisma; Ehsan, Saima; Ashraf, Mehreen; Shoukat, Nimra; Rafi, Aaisha; Naukhaiz, Hina; Nawaz, Zoia (International journal of human rights in healthcare, 2023)
Purpose The active and intentional involvement of a person in changing and developing as a person is a crucial and worth considering phenomenon that comes under the umbrella of positive psychology. There has been a previous study done on personal growth initiative (PGI) but that study did not explain whether this phenomenon exceeds in men or in women. Plus, previous studies were confined to college students only. This study aims to assess how gender influences PGI, to validate the psychometric properties of the PGI scale and to evaluate the relationship of PGI with mental well-being, career orientation and to examine whether this factor dominates in men or women and to critically validate at what age an individual starts initiating personal growth. The other main objective of the study is to work on the limitations and gaps left in previous studies on PGI by establishing a psychometrically reliable and valid scale/instrument. Design/methodology/approach To develop a scale, first, focus group discussions were conducted with six groups. Through random sampling, a sample of 50 men and 50 women were taken for the pilot study and N = 449 (156 men and 293 women) for the main study with ages ranging from 18 to 35 years were taken (M = 42.30, SD = 12.61). The study consisted of focus group discussions followed by thematic analysis and item pool generation which further followed the main study analysis. For the development of the scale, a theoretical basis along with focus group discussion was conducted to establish an item pool of 123 items. Afterward, 7 experts in the surroundings examined those 123 items to perform subject expert matter to establish content validity. Mixed method was used as a research method in which exploratory sequential design was used. Focus groups were used as a data collection technique. Random sampling is used to collect participants for study/methodology/approach – the study consisted of focus group discussions followed by thematic analysis and item pool generation which further followed the main study analysis. A 19 item five-point Likert-type scale is constructed for public administration on a sample of N = 449 (men = 156 and women = 293). Alpha reliability of the scale (0.83), Kaiser-Meyer-Olkin (KMO) (0.88) and Bartlett’s, psychometric properties of study variables skewness (0.47), kurtosis (−0.17). Inter item correlation matrix, item-total correlation, Scree plotting, t-test (t = −1.90) and (p = 0.05) and linear regression analysis are analyzed on the data and items. This scale is kept parsimonious so that it could be understood by the general population as well. Findings A 19 item five-point Likert-type scale is constructed for public administration on a sample of N = 449 (men = 156 and women = 293). High Alpha reliability of the scale (a = 0.83), KMO (0.88) and Bartlett’s, psychometric properties of study variables skewness (0.47), kurtosis (−0.17). Inter item correlation matrix, Scree plotting, t-test (t = −1.90) and (p = 0.05) and linear regression analysis are analyzed on the data and items. Three factors i.e. effectiveness, shaping and aptitude were formed through exploratory factor analysis (EFA). KMO value of 0.88 suggests that the sample is sufficient to perform EFA. Regression analysis suggests that gender is positively predicting PGI as results are statistically. Research limitations/implications Some of the limitations of this scale on which the future researchers can work are that the sample included participants above age 18 only, so for future researchers they could include participants below this age and find out the PGI factor in them. The sample also included mostly unmarried individuals so for future applications they can find out the extent to which being married can affect the PGI factor, as compared to being unmarried. Another thing that should be mentioned is that the main objective was to find out whether PGI differs among men and women and as the results show that it does differ on the basis of gender but for future studies, the researchers could work on if there is also a difference in men and women in the three subscales (formed during EFA). Practical implications This scale is developed using a significant element of human personality called personal growth which is applicable to various categories and settings of the society to measure the aptitude and inclination toward PGI. This scale can be eligibly administered for research purposes for measuring the growth attitude as a reliable predictor in suitable combination with other expected variables like career development. Originality/value The findings suggest the instrument to be psychometrically valid and reliable and can be helpful in many domains such as industrial organizations, career counseling areas and clinical and research settings. Also, the instrument can be beneficial for future studies in identifying other possible relationships with multiple variables. The current study is an original work to assess the level of PGI in men and women as the previous studies did not include participants below 25 and also they did not assess the inclination of PGI comparably in men and women.